Dr. Petros Christodoulou — Deep Plane Facelift — Prague - Christodoulou, Petros (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Petros Christodoulou, practicing in Prague, Czech Republic. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003433; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; czech republic; prague